A novel rat model to determine interaction between reflux oesophagitis and bronchial asthma. Issue 5 (25th January 2008) - Sugawa, T; Fujiwara, Y; Yamagami, H; Watanabe, K; Tanigawa, T; Shiba, M; Watanabe, T; Tominaga, K; Oshitani, N; Higuchi, K; Arakawa, T
Abstract : Background: Several studies have shown a strong association between reflux oesophagitis (RO) and bronchial asthma (BA). The precise mechanisms of interaction between RO and BA are uncertain, possibly due to lack of animal models. Aims: We established a novel rat model and examined pathogenic interaction of RO and BA. Methods: RO and BA were induced in Brown–Norway rats by ligating the transitional region between the forestomach and the glandular portion and wrapping the duodenum near the pylorus, and by ovalbumin (OVA) sensitisation and challenge with OVA aerosol. Rats were divided into four groups: control, RO, BA, and RO+BA. OVA-induced airway inflammation was assessed by the number of infiltrating cells and cytokine levels in bronchoalveolar lavage fluid (BALF). Oesophageal lesion index, histology and expression of cytokine mRNA, as determined by real-time RT-PCR, were also examined. Results: Significant increases in the number of cells, especially eosinophils, and IL13 but not IFN-γ concentration in BALF were observed in the RO+BA group compared with the BA group. These enhancements of OVA-induced airway inflammation were prevented by treatment with rabeprazole. Although the oesophagitis lesion index in the RO+BA group did not differ from that in the RO group, eosinophilic infiltration in the oesophageal submucosa and levels of mRNA expression of cytokines such as IL5, IL10, IL13, and RANTES were significantly increased. Conclusion: We established a novel rat model of RO and BA, and found significant interactions of the two diseases. This model thus appears to be useful for examining the association between gastro-oesophageal reflux disease and bronchial asthma.